Social and Cultural Change due to Social Media Instagram for Students - Andi Sadriani (Jurnal Sosialisasi: Jurnal Hasil Pemikiran, Penelitian dan Pengembangan Keilmuan Sosiologi Pendidikan, 2023)
This study aims to find out how socio-cultural changes occur in students due to the use of Instagram. This study used a qualitative research type using a descriptive approach by taking as many as 25 informants who were selected using a purposive sampling technique. Research data were collected by means of observation, interviews, and documentation. Data analysis techniques include word redaction, data presentation, and drawing conclusions. The results of the study show that the culture of communicating via Instagram has another impact on students in Makassar City. A very visible impact is the use of Instagram by female students, with a duration of 3 hours and some even up to 24 hours a day. This can indirectly change the pattern of social interaction among fellow students in communicating.